Application of GIS Based Re-Settlement of Land Record of Mouza Shahbat Khel, District Mardan (Pakistan) (Journal of Asian Development Studies, 2024)
A cadastral information system is a set of processes for parcel/property-based data collection, including land tenure, land use, and land value. The primary goal of the Massavi maps at the time was to depict the distribution, status, and yield of arable fields; other information (such as rivers) was relatively inaccurately drawn, leading to geometrical inaccuracies. It results in a significant loss for revenue collection and other objectives. Secondly, It is difficult to overemphasize how necessary knowledge is to the success of any planning, development, or management work. Having a reliable knowledge base is especially crucial for developing countries with limited resources. Another issue that many developing nations encounter is the lack of accurate land records in the real estate market. The cause can include ownership titles, unclear boundaries between private and collective rights, etc. Thus, there is an urgent need to focus on the creation and deployment of a national digital cadastral information system. Given the preceding context, this article outlines all the obstacles and limits that would arise when combining geometric and legal cadastral data to create a new digital cadastral system. A digital cadastral land information system comprises spatial data that represent legal boundaries of land parcels and provides a vital base layer for integration into other spatial Information systems or as a standalone solution that permits users to retrieve, create, update, store, view, analyze and publish land information.